Analysis of carbonation and hydration of BOF steel slag for application as railway ballast - Fernandes,Daniel Pinto (2020)
Abstract The reutilization of waste is a valuable alternative for the preservation of natural resources and the environment. In this sense, Basic Oxygen Furnace (BOF) steel slag is one of the most residues generated in steel the industry. It is estimated that for each ton of steel produced, about 150 kg of steel slag is generated in the BOF process. Generally, the newly produced BOF steel slag is volumetrically unstable, presenting expansive characteristics, and for this reason, its application should be based on stabilization studies. The main objective of this research was to analyze the chemical stabilization process of BOF steel slag by means of carbonation of the material. For this purpose, an experimental method based on hydration and carbonation in 2-meter high slag piles, moistened with sprinklers and instrumented with leaf wetting, temperature, precipitation and carbon dioxide content sensors was used. A control stack was also set up to accompany the stabilization process through the conventional procedure, in which the material is disposed of in large stacks and subjected to the weather conditions for long periods. The laboratory campaigns were developed in the laboratories of the Federal University of Ouro Preto. Thus, through the results obtained, it was possible to conclude that the stabilization method based on hydration and carbonation for the BOF steel slag was efficient, reducing the free lime content to values well below those prescribed internationally.